2020
DOI: 10.1051/bioconf/20202801003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of species boundaries of Selais fish from Arut River, Central Kalimantan based on 16S mitochondrial gene using Bayesian approach

Abstract: Selais fish is difficult to discriminate with other Silurid fish species based on morphological characters. As a result, the valid species of selais fish is uncertain. Therefore, a molecular phylogenetic study was needed to clarify species boundaries and to addresses genetic relationships of the selais fish. In this study, 16S mitochondrial gene of ten selais samples collected from Arut River (Central Kalimantan) were sequenced, from which a Bayesian trees was generated. Result revealed monophyletic of selais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This was confirmed by quite a significant bootstrap value (100/98) and posterior probability (1) and the mean of genetic distance between clade A dan clade B was 3.6%. A previous study by Arisuryanti et al (2020a) described that selais fish based on the 16S mitochondrial gene were closer to genus Kryptopterus than genus Ompok with significant differences in genetic distance of 44.1% and 65.8%, respectively. This discovery has confirmed that the ambiguous name and dispels doubts of selais fish previously were still unclassified accurately.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This was confirmed by quite a significant bootstrap value (100/98) and posterior probability (1) and the mean of genetic distance between clade A dan clade B was 3.6%. A previous study by Arisuryanti et al (2020a) described that selais fish based on the 16S mitochondrial gene were closer to genus Kryptopterus than genus Ompok with significant differences in genetic distance of 44.1% and 65.8%, respectively. This discovery has confirmed that the ambiguous name and dispels doubts of selais fish previously were still unclassified accurately.…”
Section: Resultsmentioning
confidence: 89%
“…For conservation management efforts of Selais fish, especially in the Arut River, it is necessary to carry out initial data collection such as molecular identification of species names. Arisuryanti et al (2020a) reported that the boundaries status and classification by identifying the selais fish using the 16S mitochondrial gene were still undetermined due to low similarity and genetic distance values compared to the GenBank database. Although the COI mitochondrial gene is a high conserve region and highly acceptable for identification of almost all animals (Mitani et al 2009), limited data in the GenBank database (unregistered) causes a low percentage of similarity and query cover for comparison, and this is a constraint in species determination.…”
Section: Introductionmentioning
confidence: 99%